2022
DOI: 10.1039/d1qo01906f
|View full text |Cite
|
Sign up to set email alerts
|

Temperature controlled di- and monosulfonylation of propargyl alcohols with sodium sulfinates: switchable access to (E)-allyl, vinyldisulfones and propargyl sulfones

Abstract: A switchable di- and monosulfonylation of propargyl alcohols with sodium sulfinates is developed, which successfully affords (E)-allyl, vinyldisulfones and propargyl sulfones in good to excellent yields, respectively. The salient features...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…To continue the study of the sulfinamides as a sulfur nucleophile, we initially investigated the reaction between 2,4-diphenylbut-3-yn-2-ol 1a and 4-methyl-benzenesulfinamide 2a in HFIP under the catalyst-free condition. The allenyl sulfone product 3aa was detected instead of propargyl sulfone, , which was unambiguously determined by proton and carbon nuclear magnetic resonance (NMR) spectroscopy and high-resolution mass spectrometry (HRMS) (see the Supporting Information). The product 3aa was obtained with 71% isolated yield at 70 °C in HFIP under open air (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To continue the study of the sulfinamides as a sulfur nucleophile, we initially investigated the reaction between 2,4-diphenylbut-3-yn-2-ol 1a and 4-methyl-benzenesulfinamide 2a in HFIP under the catalyst-free condition. The allenyl sulfone product 3aa was detected instead of propargyl sulfone, , which was unambiguously determined by proton and carbon nuclear magnetic resonance (NMR) spectroscopy and high-resolution mass spectrometry (HRMS) (see the Supporting Information). The product 3aa was obtained with 71% isolated yield at 70 °C in HFIP under open air (Table , entry 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, to the best of our knowledge, few studies have been reported on the direct sulfonylation of propargyl alcohols in the absence of catalysts or oxidants. Loh and Xie used sulfinic acid and sodium sulfinates, respectively, as the sulfonyl reagents in direct sulfonylation of propargyl alcohol, while the propargyl sulfones were gained as the sole product.…”
Section: Introductionmentioning
confidence: 99%
“…allyl vinyl disulfones) 112d and propargyl sulfones 112c via controllable di- and monosulfonylation of propargyl alcohols 112a with sodium sulfinates 112b in an aqueous medium under an air atmosphere (Scheme 112). 141 While selective disulfonylation was achieved with 2 equiv. of sulfinates at refluxed temperature, the mono-sulfonylation was realized using 1.2 equiv.…”
Section: Disulfonylationmentioning
confidence: 99%
“…Meanwhile, Zhang and Xie et al could perform two different methods by controlling the temperature in mono-and disulfonylation of propargylic alcohols 1 with sodium sulfonates 187 toward synthesizing propargyl sulfones 188 or (E)-allyl, vinyldisulfones 189, respectively (Scheme 81). [76] When the reaction was carried out at a low temperature, the OH group of secondary propargylic alcohol 1 was activated by acid, followed by the nucleophilic addition of sodium sulfonate to give propargyl sulfones 188. By increasing the temperature, the reaction of tertiary propargylic alcohol proceeded through allene sulfone B formation, which reacted with R 3 SO 2 Na 187 to give (E)-allyl, vinyldisulfone 188.…”
Section: Reaction With S Nucleophilesmentioning
confidence: 99%